Adhering to basic principles in a rare dental condition: a case report of severe dilaceration - Shahab Javanmardi; Abubaker Qutieshat (Academy Publishing Center, 2023)
Background: Dilaceration is a rare dental condition that can occur during tooth development, resulting in distortion of the normal axial relationship between the crown and root. Although it can affect any tooth, it most commonly occurs in permanent incisors, often as a result of trauma to the primary predecessor. The impact of even a slight displacement of a primary incisor can be significant, disrupting the normal development of the follicles of new permanent teeth. Despite its rarity, dilaceration can pose significant challenges for dental professionals in terms of diagnosis and treatment. Case Description: A case report of a 27-year-old female patient is presented, who attended with a missing maxillary left permanent central incisor and a hard palpable bulge in the maxillary vestibular area. Radiography revealed an impacted maxillary left central incisor, which was found to be dilacerated with a 120⁰ angle. Consequently, surgical extraction of the impacted tooth was planned as orthodontic extrusion is not a viable option in such cases. The extracted tooth was found to have no signs of resorption, and healing was progressing satisfactorily. Conclusion: Radiography is the most reliable method of detecting the condition. The report emphasizes the importance of detecting dilaceration early and adhering to basic principles for its diagnosis and management. Clinical Significance: The report provides valuable insights for dental professionals on the surgical management of severely dilacerated teeth and the need for a multidisciplinary approach due to the high risk of root fractures.   Received: 04 March 2023 Accepted: 09 April 2023 Published: 20 April 2023